Professional Clojure - Anderson, Jeremy; Gaare, Michael; Holguín, Justin; Bailey, Nick; Pratley, Timothy (Wrox, a Wiley brand, 2016)
Professional Clojure is the experienced developer's guide to functional programming using the Clojure language. Designed specifically to meet the needs of professional developers, this book briefly introduces functional programming before skipping directly to the heart of using Clojure in a real-world setting. The discussion details the read-eval-print workflow that enables fast feedback loops, then dives into enterprise-level Clojure development with expert guidance on web services, testing, datomics, performance, and more. Read from beginning to end, this book serves as a clear, direct guide to Clojure programming-but the comprehensive coverage and detail makes it extraordinarily useful as a quick reference for mid-project snags. The author team includes four professional Clojure developers, ensuring professional-level instruction from a highly practical perspective.